Developing regional approach for transport industry: the role of port system in the Balkans - Beškovnik, Bojan; Twrdy, Elen (Transport, 2015)
The paper presents a wider perspective on possibilities to develop a regional strategy for efficient management of the transport industry in the region of the Balkans. The focus is mainly on ports, their actual and future role in transport industry and regional economy. A complete overview of the actual situation of port industry and inland infrastructure is presented. Based on a seven pillar model, other key elements, such as Information Technology (IT) systems in use, documentary procedures and managing strategies of ports in the Balkans were analysed. The main proposal is connected to the development of a regional role for ports on the eastern coast of the Adriatic Sea in order to secure port regionalization and specialization. On this basis, the inland infrastructure and other supporting elements as IT platforms and documentary procedures should be developed accordingly. The entire region and economy should benefit from such cooperation as new supply chains might be attracted.First published online: 14 Jul 2014